STRATEGI RESILIENSI PEDAGANG MUSLIM DALAM MENGHADAPI PRAKTIK RIBA: ANALISIS BERBASIS MAQASHID SYARIAH - Budiarti Lestari; Inas Septa Hidayati; Agus Waluyo; Rina Rosia (ISTISMAR, 2026)
Usury  practices in trading activities pose a systemic threat to the moral and financiaal aspects of Muslim traders. This study aims to formulate a resilience strategy model for Muslim traders facing usurious ecosystems based on Imam AsSyatibi's Maqashid Shariah perspective. The research method used is qualitative descriptive with a literature study approach (library research). The results indicate that usurious capital infiltration destroys macro- welfare pillars in the aspects of hifz ad-din, hifz al-mal, and hifz an nafs, which triggers tatfif (weight fraud). As a solution, two dimensions of resilience are formulated : the micro level through the Kulli-Juz'i Theory (barakah-oriented reframing and zuhud bisnis) and the macro level the Al Wujud bil Kul li-Hifzhil-Kulli Theory (social caapital optimization and arisan modal). In conclusion, this dual resilience model successfully breaks structural dependency on moneylenders and maintains the spiritual independence of traders. Kata kunci: Maqashid Shariah, usury, Trader Resilience, As-Syatibi.